Clipping ungueal como método diagnóstico em pacientes com psoríase e artrite psoriática - Fonseca, Gabriela Poglia (2013)
INTRODUCTION: Psoriasis affects 1-2% of world population. From 7% to 40% of patients with psoriasis develop arthropathy. Nail psoriasis is present in up to 50% of patients with psoriasis, while more than 80% of patients with psoriatic arthritis (PsA) have nail abnormalities. Nail clipping is a recent microscopical method, and its usefulness in psoriasis and psoriatic arthritis is yet to be defined. OBJECTIVE: To describe the microscopic findings of nail clipping in patients with psoriasis and PsA in comparison to controls. METHODS: Individuals with psoriasis and PsA (with or without onychodystrophy ) and controls were evaluated in a cross-sectional design. All patients were evaluated for NAPSI (Nail Psoriasis Severity Index). The clipping fragments were obtained from the distal nail plate (5 mm-length and 2 mm-width). Fragments were analysed by an expert Dermatopathologist. The chi-square and Fisher tests were used to compare categorical variables, while the Kruskal-Wallis and Mann-Whitney tests were used to compare quantitative variables. Significance level was 5%. RESULTS: Twenty patients with psoriatic arthritis and onychodystrophy (APO), 21 patients with psoriatic arthritis and normal nails (AP), 30 patients with psoriasis and onychodystrophy (PO), 25 patients with psoriasis and normal nails (P) and 22 healthy controls were studied. Mean age did not differ among groups (P=0,06). Females predominated in all groups, except for patients in group PO (P<0.01). The first fingers were the most affected in APO and PO groups. Methotrexate was used in 64.29% of patients with psoriatic arthritis and 16.36% of patients with psoriasis (P<0.01). The subungual width was higher in patients with psoriasis and PsA when compared to controls, even after adjustment for methotrexate intake (P=0.04). All patients had a higher rectified subungueal region compared to controls, even after adjustment (P<0.01). Hypereosinophily of nail plate was a relevant characteristic of control group, as confirmed after adjustment (P=0.02). Neutrophils were higher in PO group compared to the other groups, when evaluated in the adjusted estimate (P=0.04). Serous lakes were significantly more present in all groups compared to controls, a finding confirmed after adjustment (P<0.01). The adjusted estimate revelead more Civatte bodies in APO group than in the others (P<0.01). Blood cells were more frequent in PO group than in the others (P=0.05). More bacteria were seen in all groups of patients compared to controls, even after adjustment (P<0.01) while fungi were more frequent in PO group in the adjusted estimate (P=0.04). Clipping variables did not discriminate PsA from psoriasis, nevertheless (P>0.05). There was no significant correlation of variables of nail clipping with the modified NAPSI (rs<0.20, P>0.05). CONCLUSION: Nail clipping clearly distinguished patients with PsA and psoriasis from controls, but not PsA from psoriasis.